Wheel Balanced Cancer Therapy for Longer Than 21 Days Can Have a Positive Effect on the Survival of Patients with Stage IV Cancer - Hyung-Joon Jeon; Jong-min Kim; Chong-kwan Cho; Yeon-weol Lee; Hwa-seung Yoo (Korean Pharmacopuncture Institute, 2015)
Objectives: Correlations of the levels of the nonspecific inflammatory markers C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) and of the coagulation marker fibrinogen with the treatment period of wheel balanced cancer therapy were determined. Methods: Electronic charts of stage IV cancer patients hospitalized from February 1, 2008, to November 30, 2013, were reviewed retrospectively. Patients whose laboratory follow-up tests included at least two data points for at least one marker were included. Patients receiving chemotherapy or radiotherapy or having Eastern Cooperative Oncology Group (ECOG) levels exceeding 2 were excluded. Correlations of the markers with the length of treatment for treatment periods ≥ 21 and ≤ 20 days were determined by gender and whether or not surgery had been performed. Results: Analyses of the CRP and the ESR revealed a higher proportion of patients with stable marker levels than with increased or decreased levels. Also, only the ESR in female and the CRP in male groups had higher proportions of patients with stable marker levels than with increased or decreased levels. The ≥ 21 day group had a higher proportion of patients with stable CRP and ESR levels than the ≤ 20 day group. Only the ESR in female and the CRP in male groups had higher proportions of patients with stable marker levels in the ≥ 21 day than in the ≤ 20 day group. In addition, only the CRP in the surgery group and the ESR in the non-surgery group had higher proportions of patients with stable marker levels in the ≥ 21 day group than in the ≤ 20 day group. Conclusion: For stage IV cancer patients at hospitals that offer Korean medicine, more than 21 days of long-term wheel balanced cancer therapy (WBCT) should help maintain the CRP and the ESR levels and should have a favorable effect on the survival rate.